Meningkatkan Inovasi pada Badan Usaha Milik Desa (BUMDes) Berbasis Pariwisata: Modal Manusia dan Sosial, Budaya Organisasi, serta Proses Manajemen Pengetahuan - Ahmad; Rd. Tuty Sariwulan; Sri Indah Nikensari (The Asia Pacific Journal Of Management Studies, 2025)
This study examines the effect of human and social capital-supporting human resource (HR) practices and structural capital-supporting culture on innovativeness, as well as the mediating role of knowledge management (KM) processes in tourism-based Village-Owned Enterprises (BUMDes) in Lebak Regency. Using a quantitative approach, data were collected from 387 employees across 30 BUMDes through a structured questionnaire survey. The data were analyzed using structural equation modeling (SEM) with AMOS 26 software. The findings indicate full mediation of KM processes between human capital-HR (HCHRP), social capital-HR (SCHRP), bureaucratic culture (BOC), and innovativeness. KM processes partially mediated the effect of innovative-competitive culture (IOC) on innovativeness. KM processes exhibited a strong predictive capacity for innovativeness, suggesting that HR practices supporting human capital and an innovative-competitive culture significantly contribute to KM processes and employees’ innovativeness in BUMDes, respectively. This study provides practical insights for HR and knowledge managers in BUMDes to leverage HR practices and organizational culture to enhance both employee and organizational innovative performance. Furthermore, the study contributes to the literature on intellectual capital and knowledge.